2019
DOI: 10.1088/1674-1056/28/3/037102
|View full text |Cite
|
Sign up to set email alerts
|

Magnetochemistry and chemical synthesis

Abstract: High magnetic field is one of the effective tools to control a chemical reaction and materials synthesis. In this review, we summarized the magnetic field effects on chemical reactions, such as reaction pathway, growth behavior of nanomaterials, product phase, and magnetic domain of materials. The surface spins and activity of catalysts under magnetic fields were also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Another significant physical force that controls chemical reactions is the magnetic field. In recent years, numerous chemical systems with diverse magnetic field intensities have been used to study a wide range of magnetic field effects on chemical reactions [6] . In addition to chemical, electrical, and magnetic field alterations, molecules may be closely coupled to light to alter their chemical and physical characteristics [98] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another significant physical force that controls chemical reactions is the magnetic field. In recent years, numerous chemical systems with diverse magnetic field intensities have been used to study a wide range of magnetic field effects on chemical reactions [6] . In addition to chemical, electrical, and magnetic field alterations, molecules may be closely coupled to light to alter their chemical and physical characteristics [98] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous chemical systems with diverse magnetic field intensities have been used to study a wide range of magnetic field effects on chemical reactions. [6] In addition to chemical, electrical, and magnetic field alterations, molecules may be closely coupled to light to alter their chemical and physical characteristics. [98] Light is a constant example of how nature uses magnetic and electric fields in the form of electromagnetic radiation.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a type of important thermodynamic parameter, the magnetic field has been extensively utilized to manipulate the morphology, structure, and product phase during the synthesis and growth of the nanomaterials [21][22][23][24]. For instance, Ding et al have demonstrated a magneto-hydrothermal approach to prepare pure and stable 1T-MoS 2 nanosheets.…”
Section: Introductionmentioning
confidence: 99%